2005
DOI: 10.1016/j.bbmt.2005.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Incidence, Clinical Features, and Outcome of Symptomatic Upper and Lower Respiratory Tract Infections by Respiratory Viruses in Adult Recipients of Hematopoietic Stem Cell Transplants for Hematologic Malignancies

Abstract: Respiratory viruses (RVs) are known to be major causes of morbidity and mortality in recipients of hematopoietic stem cell transplants (HSCTs), but prospective long-term studies are lacking. We prospectively screened all adult HSCT recipients (172 allogeneic [alloHSCT] and 240 autologous [autoHSCT]) who underwent transplantation during a 4-year period (1999 to 2003) for the development of a first episode of symptomatic upper respiratory tract infections and/or lower respiratory tract infections (LRTI) by an RV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
195
5
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(217 citation statements)
references
References 65 publications
10
195
5
2
Order By: Relevance
“…17,19 With regard to disease severity, progression to pneumonia is frequent and has been more frequently reported in allogeneic than in autologous HSCT recipients with hMPV infection. 6,7 In the present series, 3 of the 11 patients (27.3%) with hMPV infection developed pneumonia. However, we could not establish the role of hMPV in one episode because RSV was also detected in the same BAL sample.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…17,19 With regard to disease severity, progression to pneumonia is frequent and has been more frequently reported in allogeneic than in autologous HSCT recipients with hMPV infection. 6,7 In the present series, 3 of the 11 patients (27.3%) with hMPV infection developed pneumonia. However, we could not establish the role of hMPV in one episode because RSV was also detected in the same BAL sample.…”
Section: Discussionmentioning
confidence: 90%
“…The present study demonstrated a prevalence rate of 7% of hMPV infection in HSCT recipients with upper respiratory symptoms during 3 consecutive years. In a prospective 4-year study, Martino et al 6 found a 2-year incidence of 5.2 and 3% in allogeneic and autologous HSCT recipients, respectively. In our series, the prevalence rate reached 11% in 2003, probably reflecting greater intensity of hMPV circulation in the community that year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 H1N1 in allogeneic stem cell recipients: courses of infection and influence of vaccination on graft-versus-host-disease (GVHD) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 It is well known that seasonal influenza causes substantial morbidity and mortality in immunocompromised allogeneic blood stem cell recipients. 1 groups. The experiences demonstrate that by taking all available measures it might be possible to …”
Section: To Cite This Versionmentioning
confidence: 99%
“…1,2 Although the majority are upper respiratory tract infections, [1][2][3][4][5] pneumonia historically occurs in 16-45% of all RV episodes, [1][2][3] and up to 80% of influenza. 6 Early treatment with oseltamavir has been shown to reduce the incidence of pneumonia in cases of influenza to o30% with an associated mortality o10%.…”
Section: Introductionmentioning
confidence: 99%